Social Media in Russian Politics - Salikov, Alexey (Politologija, 2020)
This paper considers the issue of the influence of social media on politics in Russia. Having emerged in the late 1990s as a tool for informal communication, social media became an important part of Russian socio-political life by the end of 2010s. The past two decades is a sufficient period of time to draw some intermediate conclusions of the impact of social media on the political development of the country. To do this is the main goal of the paper. Its main body consists of three parts. The first chapter gives a general characterization of Russian social media, its significance in terms of influencing the formation of public opinion, public debate, and the socio-political agenda in the country. The second chapter examines the use of social media by the Russian opposition and protest movements. The third chapter analyses the use of social media by the Russian authorities.
Keywords: social media; politics; political communication; public sphere; Russia; Russian authorities; Russian opposition